Improving turbine endwall cooling uniformity by controlling near-wall secondary flows - Thomas, M; Povey, T (SAGE Publications, 2016)
In this paper, we propose a design philosophy for cooling high-pressure nozzle guide vane endwalls, which exploits the momentum of cooling jets to control vane secondary flows thereby improving endwall cooling uniformity. The impact of coolant-to-mainstream pressure ratio, hole inclination angle, hole diameter, vane potential field, and overall mass flux ratios are considered. Arguments are developed by examining detailed experimental studies conducted in a large-scale low-speed cascade tunnel with engine-realistic combustor geometry and turbulence profiles. Computational fluid dynamics predictions validated by the same are used to extend the parameter space. We show that the global flow field is highly sensitive to the inlet total pressure profile, which in turn can be modified by introducing relatively low mass flow rates of cooling gas at engine realistic coolant-to-mainstream pressure ratios and mass flux ratios. This interaction effect must be understood for successful design of optimised endwall cooling schemes, an effect which is not sufficiently emphasized in much of the literature on this topic. Design guidelines are given that we hope will be of use in industry.